Utilization of Animated Cartoon Media in Increasing Students' Knowledge of Dental and Oral Health - Fitriyah; Salfiyadi, Teuku; Andriani; Linda Suryani (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
Animated cartoons are media that contain a collection of images that are processed in such a way as to move and are equipped with audio so that they are memorable and store learning messages. The purpose of this study was to determine the effect of counseling using animated cartoon media on dental and oral health knowledge. Based on the results of the initial data examination conducted on 15 students, the results obtained were 2 students with good knowledge, 2 students with moderate knowledge, and 11 students with less knowledge. This research method uses a Quasi Experiment One Group Pre test-Post test design. The population in this study were all fifth-grade students of SDN 2 Lamcot Aceh Besar totaling 30 respondents. The sampling technique used was the Total Sampling technique. This research was conducted on 12-18 May 2022. Data collection using a questionnaire. This study used the SPSS Paired Sample T-test and analyzed univariately and bivariate. Based on the results of the study, there were differences in the mean before and after the intervention with a difference in the mean value of 40.1. The results of statistical tests obtained a significance value of p = 0.000 (p = <0.05). The results of this analysis indicate that there is a significant difference between before and after counseling using animated cartoon media. It can be concluded that in this study there was an effect of counseling using animated cartoon media on dental and oral health knowledge of fifth-grade students at SDN 2 Lamcot Aceh Besar. It is recommended to teachers and health workers at the local health center use animated cartoon media in increasing students' dental and oral health knowledge.